Multicenter randomized controlled study to assess the effect of prophylactic clipping on post‐polypectomy delayed bleeding. Issue 5 (25th May 2016) - Matsumoto, Mio; Kato, Mototsugu; Oba, Koji; Abiko, Satoshi; Tsuda, Momoko; Miyamoto, Shuichi; Mizushima, Takeshi; Ono, Masayoshi; Omori, Saori; Takahashi, Masakazu; Ono, Shoko; Mabe, Katsuhiro; et al.
Abstract : Background and Aim: Prophylactic clipping has been widely used to prevent post‐procedural bleeding in colon polypctomy. However, its efficiency has not been confirmed and there is no consensus on the usefulness of prophylactic clipping. The aim of the present study was to evaluate the preventive effect of prophylactic clipping on post‐polypectomy bleeding. Methods: A multicenter randomized controlled study was conducted from January 2012 to July 2013 in Japan. Patients who had polyps <2 cm in diameter were divided into a clipping group and a non‐clipping group by cluster randomization. After endoscopic polypectomy, patients allocated to the clipping group underwent prophylactic clipping, whereas the procedure was completed without clipping in patients allocated to the non‐clipping group. Occurrence of post‐polypectomy bleeding was compared between the two groups. Results: Seven hospitals participated in this study. A total of 3365 polyps in 1499 patients were evaluated. The clipping group consisted of 1636 polyps in 752 patients, and the non‐clipping group consisted of 1729 polyps in 747 patients. Post‐polypectomy bleeding occurred in 1.10% (18/1636) of the cases in the clipping group, and in 0.87% (15/1729) of those in the non‐clipping group. The difference was –0.22% (95% confidence interval [CI]: –0.96, 0.53). Upper limit of the 95% CI was lower than the non‐inferiority margin (1.5%), and we could thus prove non‐inferiority of non‐clipping against clipping. Conclusion: Prophylactic clipping is not necessary to prevent post‐polypectomy bleeding for polyps <2 cm in diameter.